Clipping - Nicholas Royle (University of Edinburgh, 2008)
We are living in a new era of haunting, one in which (as the essays published here suggest) we find ourselves engaging with the 'ethics of the spectral text', 'spectral and textual haunting', and 'ghostly narrative' (as distinct from narrative about the ghostly). Such phrases themselves tell a story or at least evoke a disorder that is in keeping with this new era. They are new kinds of phrases: they seek a place, a haunt, in which spectrality cohabits with writing, text and narrative, as well as with the question of ethics.